Communication Papers of the 2019 Federated Conference on Computer Science and Information Systems 2019
DOI: 10.15439/2019f329
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Distributed HIDS for IoT Backbone Components

Abstract: Nowadays DDoS attacks using devices from IoT networks are frequent and extensive. Given that IoT network instances are distributed and deployed on the conventional Internet structure, DDoS countermeasures in IoT need to be fully distributed and coordinated all over the components that form each IoT instance. This paper presents a host-based intrusion detection system (HIDS) that was designed and prototyped to protect the components of IoT network backbones comprising conventional switches and routers, not IoT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The authors experimentally demonstrated the existence of the mimicry attacks and demonstrated the need to prevent them. In [ 96 ], the authors propose a host-based intrusion detection system that was created and prototyped to safeguard IoT devices, that make up IoT network backbones. In their approach, a set of suggested NIDS performs traditional security verification, and it engages with a controller from the host-based NIDS to enable the coordination of intrusion detection activities in response to IoT devices affected by DDoS attacks throughout the network.…”
Section: Background Of Nids In Iot and Their Classificationmentioning
confidence: 99%
“…The authors experimentally demonstrated the existence of the mimicry attacks and demonstrated the need to prevent them. In [ 96 ], the authors propose a host-based intrusion detection system that was created and prototyped to safeguard IoT devices, that make up IoT network backbones. In their approach, a set of suggested NIDS performs traditional security verification, and it engages with a controller from the host-based NIDS to enable the coordination of intrusion detection activities in response to IoT devices affected by DDoS attacks throughout the network.…”
Section: Background Of Nids In Iot and Their Classificationmentioning
confidence: 99%
“…The authors used experimental evidence to show that mimicking attacks do exist and that their prevention is necessary. The authors of [57] suggest a HIDS that was developed and designed to protect IoT devices, which form the core of IoT networks. Their method involves a group of suggested IDS that carry out conventional security verification and interact with HIDS controller to enable the coordination of intrusion detection actions in response to IoT devices targeted by DDoS attacks across the network.…”
Section: Host-based Ids For Iot Systems (Hids)mentioning
confidence: 99%
“…All of the processes get compromised by dodging the intrusion detection system with DDOS (distributed Denial of Service). 61 This attack provides access to the network control system of the Tetra Packaging Machine because it has the potential to compromise system authentication mechanisms. The results revealed three critical functionalities of the system having the potential to materialize accidents (as shown in Table 4).…”
Section: Risk Assessment Using Fmea For Tetra Packaging Case Studymentioning
confidence: 99%
“…Once recognized the hazards, the analysis reveals that the security threats (i.e., tempering the calculations of packages temperature, disturbing the evaporation process, stopping the process of gas removal, increasing/decreasing the bottle movement speed, tempering the bottle cleaning process, disturbing the sealing, cutting and wrap molding process) can introduce safety hazards. All of the processes get compromised by dodging the intrusion detection system with DDOS (distributed Denial of Service) 61 . This attack provides access to the network control system of the Tetra Packaging Machine because it has the potential to compromise system authentication mechanisms.…”
Section: Risk Management Process Demonstrated Through the Tetra Packa...mentioning
confidence: 99%